Preoperative physical training and its benefit on outcome in lung cancer surgery: Narrative review - Castrillon-Moscote, Yusneht Grein (2025)
Lung cancer constitutes the main cause of years of life lost due to cancer, being one of the most frequent and the one that generates more deaths annually in the world. Physical training prior to surgery for this cancer has shown the potential to be beneficial for patients undergoing this type of intervention. However, the evidence is heterogeneous and inconclusive. Objective: To evaluate the most recent evidence on preoperative physical training and its benefit on outcomes in lung cancer surgery. Methods: Narrative literature review where PubMed, ScienceDirect, Web of Science, and MEDLINE databases were consulted. Results: Based on the most recent evidence and compared with standard care control groups, preoperative physical training may promote both functional and surgical postoperative outcomes, especially in terms of any complications, pulmonary or severe, as well as hospital stay, forced vital capacity, forced expiratory volume, and 6-minute walk distance. Although it does not impact mortality. However, the measurement of outcomes has been heterogeneous and the methodological quality of the studies ranges from very low to moderate. Conclusions: Although the evidence is limited and heterogeneous in the measurement of functional and postoperative outcomes of preoperative physical training over surgical intervention with curative intent for lung cancer, there is a trend in favor of the latter, especially in terms of lower frequency of postoperative pulmonary complications and shorter hospital stay.